Corporate social responsibility disclosure and long run share price performance of Malaysian IPOs - Almtoor, Yasir Abdullah Abbas (2021)
This study investigates the influence of the corporate social responsibility disclosure (CSRD) and its dimensions (community, environment, workplace, and marketplace) on the long-run share price performance of 115 Malaysian IPOs listed throughout 2007-2015. To measure the IPOs’ long-run share price performance, the return measures were calculated under the equally-weighted and value-weighted schemes of the cumulative mean abnormal return (CAR) and buy-and-hold abnormal returns (BHAR) for the three post-listing years using an event-time approach. The results of this study indicate a significant overperformance and underperformance among the Malaysian IPOs when the matched companies and market are used as the benchmarks for both the IPO performance measures. The models were developed utilising the frameworks of the agency theory, the signalling theory, and the legitimacy theory to test the relationship between CSRD and its dimensions with the IPOs’ long-run share price performance. The findings of the multiple regressions showed a positive and significant association between CSRD extent and its community and environment dimensions with the IPOs’ long-run share price performance. Meanwhile, CSRD extent in the dimensions of workplace and marketplace showed a negative and significant relationship with the IPOs’ long-run share price performance. The findings of the multiple regressions showed a negative and significant association between CSRD quality and its dimensions i.e. workplace and marketplace with long-run share price performance. Meanwhile, CSRD quality in the dimensions of community and environment showed a positive and significant relationship with the long-run share price performance. The results of this study are important for investors, regulators, non-government organisations, communities, and policymakers. The findings can also enhance the understanding of companies on the importance of disclosing more CSR information to improve their performance and profitability.